Extra time for deforestation: Lessons for future EU environmental legislation - Heather Grabbe; Luca Léry Moffat (Bruegel, 2024)
Forests are essential to regulating the climate, absorbing greenhouse gases and providing fresh water and habitats for biodiversity and indigenous peoples. If deforestation continues at current rates, large parts of the planet will become uninhabitable. The European Union has only 5.5 percent of the world's population, but its demand drives 15 percent of the global forest destruction linked to trade. Therefore, the EU has introduced a law - the regulation on deforestation-free products, or deforestation regulation - to outlaw from its market products linked to deforestation. The regulation has triggered protest about its impact on trade partners, leading the European Commission to propose at short notice a delay in its implementation. However, the objectives of the regulation remain valid and important. Moreover, a large majority of EU consumers want to avoid buying products that result from deforestation and find it frustratingly difficult to find information on whether products are deforestation-free. Economic actors in most of the affected sectors support the objectives of the regulation, even though they criticise the way it has been implemented. To avoid this delay having a chilling effect on other green measures in future, the EU should learn lessons from this experience. The European Commission needs to develop a consistent and effective strategy for managing the external impact of the EU's green policy agenda, with better diplomacy towards trade partners and specific financial assistance to help the poorer countries with compliance and the transition to more sustainable production. This Policy Brief sets out why the deforestation regulation has the right objectives but needed better design and preparation for implementation. In particular, the EU needs to provide more flanking support for developing countries to ease their transitions and improve forest protection. Economic actors along the whole of supply chains need more consultation during the design stage, and the Commission needs to provide clearer guidance by sector and a well-functioning system for compliance.
Keywords: 330